Assessing Basic Income Feasibility Political Parties’ Positions on the French-Speaking Belgian Scene - Geels, Floriane (Politics of the Low Countries, 2025)
Social protection systems are under growing pressure and face many challenges. Some argue that a universal basic income (BI) has the potential to transcend political cleavages and offer the ground for a welfare reform. While previous literature has increasingly tackled BI’s feasibility, ground-based research is still scarce. This study intends to fill this gap by considering the positions of five French-speaking Belgian parties (PTB, PS, Ecolo, Les Engagés and MR) on BI. Through a qualitative in-depth analysis of semi-structured interviews and grey literature, the article shows that BI proposals coming from liberals, democrats and ecologists are representative of the left-right cleavage. This is explained by the multidimensionality of the ‘basic income’ concept but also by diverging visions on work and society. By studying concrete parties’ positions, this article reveals the barriers and ways forward the path to BI’s strategic political feasibility in Belgium.